EFFICIENCY OF THE DRUG MELDOVENS MAX (MELDONIUM DIHYDRATE AND ARGININE HYDROCHLORIDE) IN THE TREATMENT OF ELDERLY PATIENTS WHO HAVE SUFFERED MYOCARDIAL INFARCTION - Tulaboeva G. M.; Talipova Yu. Sh.; Sagatova Kh. M.; Abdukodirova N. M.; Kurbonov N. B.; Khusanov A. A.; Adilova I. G. (Web of Journals Publishing, 2025)
In elderly patients with coronary artery disease, Meldovens Max resulted in a decrease in ischemic episodes (–60%), improved physical endurance (CMT +6.5%), normalization of lipid metabolism, and decreased inflammation. Kidney function did not change. The drug demonstrated efficacy and safety as part of rehabilitation therapy.
Keywords: Ischemic heart disease, Meldovens Max, elderly patients, ischemia, lipids.